(untitled) (Revista Venezolana de Salud Pública, 2018)
Exposure to cardiovascular risk factors (CVRF) during childhood and adolescence may be associated with the development of atherosclerosis in adult life. The objective of the present investigation was to evaluate the cardiovascular risk factors in adolescents, belonging to two diversified education institutions of the Iribarren Municipality, Barquisimeto, Lara State. It was a prospective, descriptive investigation, through which clinical and paraclinical parameters were determined to evaluate CVRF, such as hypertension, dyslipidemia, obesity, overweight, sedentary lifestyle and smoking. The sampling was non-probabilistic and consisted of 136 adolescents. It was found that 38.97% of the adolescents evaluated did not present any cardiovascular risk factor and 61.09% presented one or more risk factors. Of these, 80.95 %% presented a risk factor, 11.90%) two risk factors (dyslipidemia-obesity or dyslipidemia-high blood pressure figures) and 7.15% more than three cardiovascular risk factors (dyslipidemia -obesity-high blood pressure figures-sedentary lifestyle). In the present study it was possible to establish that adolescents presented cardiovascular risk factors such as dyslipidemia, overweight / obesity, hypertension, physical inactivity and smoking. The presence of a family history of cardiovascular disease was recorded. Consequently, it is necessary to promote opportunities for intervention in the prevention and control of cardiovascular disease with actions aimed at health promotion must be incorporated at the national and community level, through mass communication educational campaigns aimed at tobacco, healthy eating and physical activity, both in parents and in children and adolescents.